Sikkim State Draft Annual Plan 1983-84 - Planning Commission (Planning Commission, 1983)
The year 1983-84 is the penultimate year of the 6th plan end consequently the investment in the plan should he mode in such a way that by 1984-85 the physical targets of the 6th plan are achieved. In order to maintain the tempo of development that has been built up through years 1980-81 to the current financial year the plan for 1983-84 envisages a step up in investment by about 25 % and accordingly the investment in the public sector for the State is proposed at Rs. 31 .75 crores.
Government of Sikkim, Planning and Development Department